2015
DOI: 10.1007/s10067-015-3043-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tripterygium glycosides tablet in treating ankylosing spondylitis: a systematic review and meta-analysis of randomized controlled trials

Abstract: Hundreds of randomized controlled trials (RCTs) on tripterygium glycosides tablet (TGT) in the treatment of ankylosing spondylitis (AS) have been published, but the therapeutic effects have never been systematically reviewed yet. The aim of this meta-analysis was to evaluate the efficacy of TGT on AS based on RCTs. PubMed, ScienceDirect, Cochrane Library, China Journals Full-text Database, and Wanfang Data were searched. The RCT quality was evaluated by the Cochrane Collaboration's tool for assessing risk of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…(TWHF), known as “lei gong teng” or “duan chang cao,” is a traditional Chinese medicine, which has been used to treat a variety of autoimmune and inflammatory diseases for decades in China . Tripterygium preparations (TPs), such as Tripterygium wilfordii tablets (TWT), Tripterygium hypoglaucum tablets (THT), and Tripterygium glycosides tablets (TGT), have been frequently used in Chinese hospitals to treat rheumatoid arthritis, systemic lupus erythematosus, and glomerulonephritis . However, the therapeutic window of most TPs is narrow.…”
Section: Introductionmentioning
confidence: 99%
“…(TWHF), known as “lei gong teng” or “duan chang cao,” is a traditional Chinese medicine, which has been used to treat a variety of autoimmune and inflammatory diseases for decades in China . Tripterygium preparations (TPs), such as Tripterygium wilfordii tablets (TWT), Tripterygium hypoglaucum tablets (THT), and Tripterygium glycosides tablets (TGT), have been frequently used in Chinese hospitals to treat rheumatoid arthritis, systemic lupus erythematosus, and glomerulonephritis . However, the therapeutic window of most TPs is narrow.…”
Section: Introductionmentioning
confidence: 99%
“…TwHF contains several active ingredients which affect multiple targets and pathways in the progression of IgAN and has been used as an adjuvant on IgAN treatment (11). A wide spectrum of biological activities about TwHF including anti-inflammatory, immunosuppressive, antioxidation, and antifibrosis has been demonstrated (9,(23)(24)(25)(26). Triptolide, a diterpenoid trioxide, is the most abundant and pharmacologically active of the metabolites found in TwHF extracts and is primarily responsible for the anti-inflammatory and immunosuppressive effects of TwHF preparation (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Data increasingly has been showing that the related extracts of TwHF have immunomodulatory, anti-inflammatory and anti-allergic effects, and is widely used for the treatment of rheumatoid arthritis in China ( Bao and Dai, 2011 ; Bai et al, 2020 ; Hu et al, 2019 ). The results of mutiple clinical trials have demonstrated that TwHF monotherapy exhibits good efficacy in patients with active RA ( Lv et al, 2015 ), SLE ( Liu et al, 2014 ; Chen et al, 2020a ), ankylosing spondylitis ( Li et al, 2015 ; Ji et al, 2015 ), kidney disease ( Ge et al, 2013 ; Wang, 2018 )and some skin diseases, such as psoriasis ( Lv et al, 2018 ). Zhang et al found that TwHF can disrupt the process of CTD-ILD through multiple targets and multiple pathways ( Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%